Perancangan dan Pembuatan Aplikasi Sistem Informasi Perpustakaan Yayasan X - Yuril Adrian Manoppo; Kartika Gunadi; Djoni Haryadi Setiabudi (Jurnal Infra, 2014)
Organization X is currently using a manual system to manage the execution of procurement. The system, however, is ineffective to the efficiency and human error in the process of recording and loss of collections. Analyzing this problem, a new application was designed to assist with the workflow in Organization X. The application supports the lifecycle in the library trough circulation, maintenance, and reports. The application is using Microsoft Visual Studio 2010 for programming language and Microsoft SQL Server 2005 as data storage media. Based on the results of tests performed, the application could launch collection monitoring and manage the opname book. The application is open for develop with more features in the future such as automatic printing for borrowing slip and booking order by phone